2019
DOI: 10.1016/j.arthro.2019.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Anteromedial Portals in Elbow Arthroscopy: A Systematic Review of Cadaveric Studies

Abstract: Purpose: To systematically review available literature comparing location and safety of two common anteromedial portals with nearby neurovascular structures in cadaveric models and to determine the correct positioning and preparation of the joint prior to elbow arthroscopy. Methods:The review was devised in accordance with PRISMA guidelines. Inclusion criteria consisted of original, cadaveric studies performed by experienced surgeons on male or female elbows evaluating anteromedial portal placement with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
1
15
1
2
Order By: Relevance
“…This position, which is slightly more anterior than usually described positioning, allows better visualization of the joint and has been shown in cadaveric studies to put fewer structures at risk. 17 This more anterior portal also is extremely effective in arthritic elbows in allowing correct access into the joint. Tip #2: In arthritic elbows move both medial and lateral portals 0.5 mm more anterior to prevent the osteophytes from mis-directing the cannula out of the joint On the lateral side a modified anterolateral portal is used, which is established 2 cm proximal and 2 cm anterior to the lateral epicondyle.…”
Section: Portal Placementmentioning
confidence: 99%
“…This position, which is slightly more anterior than usually described positioning, allows better visualization of the joint and has been shown in cadaveric studies to put fewer structures at risk. 17 This more anterior portal also is extremely effective in arthritic elbows in allowing correct access into the joint. Tip #2: In arthritic elbows move both medial and lateral portals 0.5 mm more anterior to prevent the osteophytes from mis-directing the cannula out of the joint On the lateral side a modified anterolateral portal is used, which is established 2 cm proximal and 2 cm anterior to the lateral epicondyle.…”
Section: Portal Placementmentioning
confidence: 99%
“…Hackl et al demonstrated that the distance of the median nerve to the anterior tip of the coronoid and to the anterior border of the trochlea significantly increases from extension to 90° flexion [25]. These findings were supported by a recent review of cadaveric studies, which concluded that the distended elbow in a 90° flexed position minimizes the risk for neurovascular injury with the arthroscope [26].…”
Section: Discussionmentioning
confidence: 92%
“…For the median nerve, reliable landmarks have scarcely been reported, mostly by studies performed in arthroscopic settings and focused on defining anatomical relations at the level of the joint line, without investigating more distal regions. [13,17,18,[25][26][27][28][29]. Nevertheless, knowledge of median nerve position and behavior is essential in complex open surgery and revision cases and constitutes a precious help for all surgeons dealing with medial approaches, especially if lacking in a dedicated subspecialistic training on elbow surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A distalization of the AM portal can be conducted rather safely, with only a moderate risk of endangering the brachial artery and the median nerve, which lie more superficially, between the muscle bellies of the biceps brachii and the brachialis, and follow the medial border of the biceps brachii in an anterolateral direction. Nevertheless, elbow flexion and fluid joint distension are recommended to increase the distance of the median nerve to the anterior tip of the coronoid and to the anterior border of the trochlea, reducing the risk for neurovascular injuries during placement of medial portals [5,9,10]. Regarding the role of forearm rotation, conflicting results have been published, and no clear evidence exists to recommend a specific position (Fig.…”
Section: Medial Portalsmentioning
confidence: 99%